Subcutaneous glomus tumor of chest wall (Indian Journal of Case Reports, 2018)
Glomus tumors are known to occur in the subungual region of fingers. Extradigital occurrences have been reported in the past but are rare. Occurrence in the anterior chest wall has not been reported. We report a case of subcutaneous glomus tumor occurring in the anterior chest wall in a 47-year-old gentleman, suffering from pain for 2 years without diagnosis, who was successfully treated by excision biopsy.